2021
DOI: 10.3390/diagnostics11040657
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes between P1 and P0 Lesions for Obscure Gastrointestinal Bleeding with Negative Computed Tomography and Capsule Endoscopy

Abstract: Background: A simple classification for the relevance of lesions (P0, P1, and P2; no bleeding potential, less likely to bleed, and more likely to bleed, respectively) based on capsule endoscopy (CE) findings has been used. This study aimed at investigating rebleeding rates and predictive factors of P0 and P1 lesions after obtaining negative findings in both, CE and computed tomography (CT), for patients with obscure gastrointestinal bleeding (OGIB). Methods: Among 193 patients resulted in negative CE findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, in the long-term, recurrence of bleeding is not uncommon 53 54 55 , and further investigations could be required. In these cases, repeating the diagnostic workup by SBCE appears to have more diagnostic value than DAE; a small study from Japan showed that the rate of positive findings in the repeat SBCE group was significantly higher than in the DBE group 56 .…”
Section: Suspected Small-bowel Bleedingmentioning
confidence: 99%
“…However, in the long-term, recurrence of bleeding is not uncommon 53 54 55 , and further investigations could be required. In these cases, repeating the diagnostic workup by SBCE appears to have more diagnostic value than DAE; a small study from Japan showed that the rate of positive findings in the repeat SBCE group was significantly higher than in the DBE group 56 .…”
Section: Suspected Small-bowel Bleedingmentioning
confidence: 99%
“…17 Thus, they concluded that the rebleeding rates of the P0 and P1 groups did not differ. 17 However, we hypothesized that the risk of rebleeding would differ between patients with no abnormalities and those with minor small-bowel abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] However, definitions of negative CE findings vary among reports; most define "negative" as P0 or P1, although some define "negative" as P0 only. [12][13][14][15][16][17] Moreover, rebleeding rates of patients with negative CE findings vary widely among reports, ranging from 4.8 % to 50%. [11][12][13][14][15][16][17] Few reports compare long-term outcomes of P0 and P1 OGIB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations